Testando a hipótese do cérebro social: modelo Frieseomelitta varia - Santos, Gabriele David Dos (2019)
The social brain hypothesis states that the brain of social species would have evolved in response to environmental influences, such as competition, protection, and food demand, resulting in cooperation between individuals and increased social complexity. In this way, there are cognitive challenges that solitary species do not face. This hypothesis has been studied in vertebrates, particularly in humans and birds. Social insects have some commonalities in their biology, like the existence of division of reproductive labor, with one or a few females taking care of eggs production (queens) and the rest developing activities in maintenance of the colony (workers). In Apis mellifera bees, adult female workers have brains and brain regions proportionally larger than queens, suggesting that in this species the social brain hypothesis is valid, since the investment in brain development allows the members of this caste to perform well varied within the colony. In addition, studies from our laboratory have shown that a group of differentially expressed genes among the castes mediate the differential neurogenesis in these insects. In this work we evaluate the reach of the social brain hypothesis in bees, testing it on the native bee Frieseomelitta varia, another social species. We hypothesized that in this bee caste differences are promoted by morphological and developmental trade-off, as occurs in Africanized bees. Thus, our goal was to determine the morphogenetic and molecular patterns of post-embryonic brain development in F. varia, using histological inclusion techniques for morphometry, and molecular biology assays to determine the transcriptional profile of the selected genes. Our morphological results showed that the total brain volume in Ne workers is higher when compared to queens in the same phase. Mushroom bodies and peduncular bodies also showed interesting results, the volume of left hemisphere neurons being larger than those of workers. Some studies indicate that the left hemisphere would be related to long-term memory, an interesting fact because it is workers, who perform many functions within a colony. Three of the nine neurogenic genes that in A. mellifera are casta-specific (amci, amd and SPH41) are possible candidates for orthologous genes between F. varia and human. These genes can act in the maintenance and development nervous system already in the beginning of the embryogenesis, and in the synthesis of metabolites involved in nervous and cognitive processes of bees like dopamine and serotonina. Our molecular data showed that hex70b and hex70c are more transcribed in workers' brain at early pupal development (Pp), suggesting that these proteins in F. varia guide the development of workers even in the post-larva stages; the amci was also more expressed in workers Pp, thus remaining until Pbm. This result evidences the role of serine proteases during the formation of the nervous system, which may contribute to the greater development of the brain of workers and possibly participate as a regulator of the synaptic functions necessary for the development and improvement of cognition in workers. Our results allow us to conclude that the social brain hypothesis is applied to both A. mellifera and F. varia and the morphological differentiations of the brain are promoted by the differential expression of neurogenic genes, some of them functionally conserved in bees and vertebrates.